Peningkatan Kompetensi Guru Ekonomi di Kabupaten Malang dalam Analisis Butir Soal - Vidya Purnamasari; Muhammad Hasyim Ibnu Abbas; Dwi Wulandari; Inayati Nuraini Dwiputri (Jurnal Pengabdian Pada Masyarakat, 2021)
IMPROVING THE COMPETENCE OF MALANG’S ECONOMICS TEACHERS IN ITEM ANALYSIS. Comprehensive assessment used to measure learning outcomes is a very important component of lesson planning. In general, teachers often make mistakes in identifying the parameters used in measuring learning outcomes. In addition, the method of measuring learning outcomes with conventional methods through manual calculations can also affect the validity of learning evaluation results. This community service aims to provide training to teachers in Turen, Malang Regency on how to measure the evaluation of learning outcomes by using a more effective and efficient way, using statistical data processing software. The use of this statistical software will make it easy for teachers to be able to analyze the level of difficulty of the questions made, the effectiveness of presenting the answer choices, the analysis of the difference in each question and the analysis of the tricks. The result of this service activity is that the participants who are teachers are able to perform analysis quickly and accurately using statistical software. In addition, this training is also useful for teachers who are developing research instruments.